Design and Numerical Simulation of a High Speed Centrifugal Compressor. Issue 1 (March 2020) - Yu, Qingyang; Wu, Peng; Deng, Yelin
Abstract: The issue of energy consumption has attracted worldwide attention, therefore the performance requirements of rotating machinery are getting higher and higher in modern commercial run. Active magnetic bearings have the advantages of high speed and low friction, so they are widely used in high-speed rotating machines such as high-speed centrifugal compressors. A stage of impeller and diffuser was designed. Numerical simulations of the flow field were performed using CFX. The pressure and velocity field in the model stage (impeller and diffuser) were obtained and analyzed. The results show that the model stage has uniform velocity field distribution and regular flow field, and the performance parameters can well meet the industrial requirements.